Policy Instruments for Health Promotion: A Comparison of WHO Policy Guidance for Tobacco, Alcohol, Nutrition and Physical Activity - Peter Gelius; Sven Messing; Antonina Tcymbal; Stephen Whiting; João Breda; Karim Abu-Omar (International Journal of Health Policy and Management, 2022)
Background  Policy is an important element of influencing individual health-related behaviours associated to major risk factors for non-communicable diseases (NCDs) such as smoking, alcohol consumption, unhealthy eating and physical inactivity. However, our understanding of the specific measures recommended in NCD prevention policy-making remains limited. This study analysed recent World Health Organization (WHO) documents to identify common policy instruments suggested for national NCD prevention policy and to assess similarities and differences between policies targeting different health-related behaviours. Methods  Evert Vedung’s typology of policy instruments, which differentiates between regulatory, economic/fiscal and soft instruments, served as a basis for this analysis. A systematic search on WHO websites was conducted to identify documents relating to tobacco, alcohol, nutrition and physical activity. The staff of the respective units at the WHO Regional Office for Europe conducted an expert validation of these documents. The resulting documents were systematically searched for policy instruments. A word frequency analysis was conducted to estimate the use of individual instruments in the different policy fields, followed by an additional in-depth coding and content analysis by two independent reviewers. Results  Across all health-related behaviours, the following policy instruments were suggested most frequently in WHO guidance documents: laws, regulations, standards, taxes, prices, campaigns, recommendations, partnerships and coordination. The analysis showed that regulatory and economic/fiscal policy instruments are mainly applied in tobacco and alcohol policy, while soft instruments dominate in the fields of nutrition and especially physical activity. Conclusion  The study confirms perceived differences regarding recommended policy instruments in the different policy fields and supports arguments that “harder” instruments still appear to be underutilized in nutrition and physical activity. However, more comprehensive research is needed, especially with respect to actual instrument use and effectiveness in national- level NCD prevention policy.